Are Gcg Effectıve In Mıtıgatıng Earnıngs Management And Influencıng Csr In Famıly Fırms? - Iskandar Itan; Merinda Wijaya (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2021)
This study aims to examine the effectiveness of the role of corporate governance on corporate social responsibility (CSR) in family firms with earning management as the moderating variable. The data used in this study are secondary data of 120 family firms listed on the Indonesian Stock Exchange for the period 2015 to 2019, analyzed using Smart PLS software. In this study, the corporate governance mechanism is measured with: independent board of commissioners, institutional ownership, the board of director size, managerial ownership, and audit size. CSR is measured using the ISO 26000 standard. Meanwhile, earnings management is measured using discretionary accruals of modified Jones models. The results show that the role of corporate governance positively affects earnings management in family firms. Further analysis shows that corporate governance also influences CSR. This study also provides empirical evidence that earnings management enhances the relationship between corporate governance and CSR.